Understanding the Educational Lives of Community College Students: A Photovoice Project, a Bourdieusian Interpretation, and Habitus Dissonance Spark Theory - Amanda O. Latz (Arizona State University, 2012)
Too little research exists that provides windows into the day-to-day lives of community college students. The purpose of this paper is to explicate one finding and concomitant grounded theory derived from a photovoice project aimed at understanding the educational lives of community college students. Participants saw the community college as a means to obtain a freer life, in the broadest sense. An integration of Bourdieusian thought and scholarship on role theory led to the creation of a constructivist grounded theory termed habitus dissonance spark theory, which suggests that community college enrollment is prompted by habitus dissonance, or discomfort with perceived levels of social agency, or freedom, in life. This paper outlines the finding and resultant grounded theory and its implications.